Message - Abdullah, Dr. Asia Selman (Universal Journal of Pharmaceutical Research, 2018)
It is a great honor for me to be associated with the Universal Journal of Pharmaceutical Research (UJPR). I would like to extremely congratulate all the UJPR team for completing approx. two successful years since the establishment of the journal. I take this opportunity to thank Editor-in-Chief and all the board members for their progress and success in scientific publication pathway and providing suggestions to improve the journal quality, causing a journal indexed in good indexing platforms and increase the journal articles citations. I am expecting more success for our journal to be indexed in the famous indexing such as Scopus and Thomson Reuters.